Digital Capacity Management for Sustainable Tourism: A Breakthrough in Overtourism Control in Bromo Tengger Semeru National Park - Kartini Harahap (PT FORMOSA CENDEKIA GLOBAL, 2026)
This study develops a Digital Carrying Capacity Management (DCCM) model by integrating System Dynamics Modeling (SDM), Fuzzy Multi-Criteria Decision Making (Fuzzy-MCDM), and Artificial Intelligence (AI) to address overtourism in Bromo Tengger Semeru National Park, Indonesia. Using a mixed-method explanatory sequential design, dynamic simulations with Vensim DSS 9.2 (2024–2030) indicate that the Smart Capacity Optimization (SCO) scenario outperforms the conventional business as Usual (BAU) approach, reducing tourism pressure by 35% and improving ecological carrying capacity efficiency by 28%. Fuzzy-AHP and Fuzzy-TOPSIS identify the digital dimension as the most influential factor, with the highest weights assigned to Active IoT Sensors (0.209), Data Accuracy (0.189), and AI Prediction (0.167), contributing 0.521 to overall sustainability.